“... running in more functions without the need for more courses...”: a fundamental transformation in the traditional designer-user relationship in the use of Moodle in vocational education (Research, Society and Development, 2023)
The idea of designers working with their monitors in isolation and disconnected from the context and situation is now an obsolescence. However, the paradigm still in force for projects expires in the perspective of the mere observation of monitors isolated in space, time and in the ocean of information in which we live. The projects are present in different areas of modern life, interacting with different professional profiles. However, they seem to focus on an algorithmic perspective and largely ignore the best way to support the human being in the course of action. There is little evidence that researchers who develop such (re)conceptions, or specific components of them, take a participatory approach to designing remote learning systems. Thus, this article aims to analyze the human and organizational factors that may influence the relationship between the user/teachers and the project, designing systems capable of integrating human experience into the system's functioning. The results showed the need to adapt the platforms to users, observing their notes on the look, icons, among other everyday facts, and the characteristics of each group of people who use Moodle and MConf.